Hydrogen sulfide plays an important protective role by influencing autophagy in diseases - Wang, J; Wu, D; Wang, H (Physiological research, 2019)
Autophagy can regulate cell growth, proliferation, and stability of cell environment. Its dysfunction can be involved in a variety of diseases. Hydrogen sulfide (H(2)S) is an important signaling molecule that regulates many physiological and pathological processes. Recent studies indicate that H(2)S plays an important protective role in many diseases through influencing autophagy, but its mechanism is not fully understood. This article reviewed the progress about the effect of H(2)S on autophagy in diseases in recent years in order to provide theoretical basis for the further research on the interaction of H(2)S and autophagy and the mechanisms involved.
Keywords: Cytoprotection; Animals; Humans; autofagie; cytoprotekce; gasotransmitery; proliferace buněk; lidé; ischemie; zvířata; Autophagy; Hydrogen Sulfide; Gasotransmitters; Ischemia; sulfan; Cell Proliferation